The Role of the Black Church in HIV Prevention: Exploring Barriers and Best Practices. (13th April 2016) - Bryant‐Davis, Thema; Ellis, Monica U.; Edwards, Nathan; Adams, Tyonna P.; Counts, Pamela; Arline‐Bradley, Shavon; Sadler, Keron
Abstract: Black people have the highest rate of HIV/AIDS infection in the USA, and they are less likely to access quality physical and mental healthcare. To address these disparities as outlined in the National HIV/AIDS Strategy, there is a need for culturally congruent, innovative approaches to HIV/AIDS prevention. The first multi‐denominational national study of Black faith leaders was conducted utilizing focus groups that were held in 11 US cities. The 265 participants were faith leaders who reported involvement in such prevention practices as sponsoring HIV/AIDS workshops, integrating HIV/AIDS messaging in the worship service, hosting HIV/AIDS screenings, distributing written materials about HIV/AIDS through the bulletin or flyers, pastoral counselling, advocating for policies that provide quality healthcare to the community and disseminating HIV/AIDS prevention messages through new media such as the Church website. These findings, including attention to barriers to engagement, provide insight into innovative practices that can be integrated into faith‐based HIV/AIDS prevention programming. Copyright © 2016 John Wiley & Sons, Ltd.